Heterogeneous Locking and Earthquake Potential on the South Peru Megathrust From Dense GNSS Network - Lovery, B. (2024)
The Central Andes subduction has been the theater of numerous large earthquakes since the beginning of the 21st Century, notably the 2001 Mw = 8.4 Arequipa, 2007 Mw = 8.0 Pisco and 2014 Mw = 8.1 Iquique earthquakes. We present an analysis of 47 permanent and 26 survey global navigation satellite system (GNSS) measurements acquired in Central-South Peru between 2007 and 2022 to better understand the frictional properties of the megathrust interface. Using a trajectory model that mimics the different phases of the cycle, we extract a coherent interseismic GNSS field at the scale of the Central Andes from Lima to Arica (12–18.5°S). Interseismic models on a 3D slab geometry indicate that the locking level is relatively high and concentrated between 20 and 40-km depth. Locking distributions indicate a high spatial variability of the coupling along the trench, with the presence of many locked patches that spatially correlate with the seismotectonic segmentation. Our study confirms the presence of a creeping segment where the Nazca Ridge is subducting; we also observe a lighter apparent decrease of coupling related to the Nazca Fracture Zone (NFZ). However, since the Nazca Ridge appears to behave as a strong barrier, the NFZ is less efficient to arrest seismic rupture propagation. Considering various uncertainty factors, we discuss the implication of our coupling estimates with size and timing of large megathrust earthquakes considering both deterministic and probabilistic approaches. We estimate that the South Peru segment could have a Mw = 8.4–9.0 earthquake potential depending principally on the considered seismic catalog and the seismic/aseismic slip ratio.